TSPAN4 is a prognostic and immune target in Glioblastoma multiforme - Zheng, Yue; Lang, Yuheng; Qi, Bingcai; Wang, Yuchao; Gao, Wenqing; Li, Tong (Frontiers in Molecular Biosciences, 2023)
Background: Atherosclerosis can impact cancer progression due to the cholesterol and calcium metabolism, illustrating the links between atherosclerosis and cancer metastasis. Tetraspanin 4 (TSPAN4) may help understand migrasomes in diseases and provide novel targets for treatment. Methods: TSPAN4 expression in atherosclerosis Gene Expression Omnibus (EO) dataset and multiple omics data were explored, such as enriched pathways analysis, protein-protein interaction analysis, immune subtypes as well as diagnostic and prognostic value in pan-cancer. The relationship between Glioblastoma multiforme (GBM) and TSPAN4 was further investigated. Results: Compared to control, TSPAN4 expression was upregulated in foam cells from patients with atherosclerosis and survival analysis demonstrated high TSPAN4 expression contributes to poor prognosis. TSPAN4 expression differs significantly in immune subtypes of cancers, which can be a diagnostic and prognostic target of cancers due to the high accuracy. Overall survival analysis of subgroups demonstrated that higher TSPAN4 expression had a worse prognosis and the univariate analysis and multivariate analysis demonstrated age, TSPAN4 expression, WHO grade, IDH status and histological types were independent risk factors of Glioblastoma multiforme. Conclusion: The TSPAN4 expression was associated with atherosclerosis progression and pan-cancer, especially in Glioblastoma multiforme and GBMLGG. Therefore, TSPAN4 may serve as a potential biomarker and the crosstalk between atherosclerosis and tumor progression. The results are not fully validated and further studies are still needed to validate in vivo and in vitro.